P PENINGKATAN PRODUKTIVITAS JAGUNG MELALUI PEMBERIAN EKSTRAK BONGGOL PISANG DENGAN BERBAGAI DOSIS PUPUK SP-36. - Andi Cakra Yusuf; Eka Sudartik; Sulkifli Sulkifli; Suharman Suharman (Jurnal Inovasi Pendidikan dan Sains, 2023)
The purpose of this study was to determine the increase in corn productivity through the application of banana stump extract with various doses of SP-36 fertilizer. The research was conducted in the integrated laboratory and experimental garden of Muhammadiyah Bone University, which took place in June-August 2022. This study used a divided plot design (RPT) consisting of 2 (two) treatment factors and 3 (three) replications. The first factor is Banana Bark Extract which consists of 3 levels, namely; doses of 0 ml l-1(B0), 50 ml l-1(B50) and 100 ml l-1(B100). The second factor is SP-36 fertilization which consists of 4 levels, namely SP-36 0 kg ha-1(F0 ), 50 kg ha -1 (F 50 ), 100 kg ha -1 (F 100 ) dan 150 kg ha -1 (F 150 ). Parameter yang diukur adalah tinggi tanaman, jumlah daun, luas daun, bobot segar total tanaman, bobot kering total tanaman. Pemberian ekstrak batang pisang yang dikombinasikan dengan pupuk fosfat mampu meningkatkan tinggi tanaman, jumlah daun dan luas daun tanaman. Selain itu, kadar pemupukan fosfat berpengaruh terhadap bobot segar tanaman dan bobot kering tanaman total.